Answer:
Equation:
![{x}^{2} + {y}^{2} + 2x - 2y - 35= 0](https://tex.z-dn.net/?f=%7Bx%7D%5E%7B2%7D%20%20%20%2B%20%20%7By%7D%5E%7B2%7D%20%2B%20%202x%20%20-%202y%20%20%20-%20%2035%3D%200)
The point (0,-5), (0,7), (5,0) and (-7,0)also lie on this circle.
Step-by-step explanation:
We want to find the equation of a circle with a diamterhat hs endpoints at (-3, 4) and (5, -2).
The center of this circle is the midpoint of (-3, 4) and (5, -2).
We use the midpoint formula:
![( \frac{x_1+x_2}{2}, \frac{y_1+y_2,}{2} )](https://tex.z-dn.net/?f=%28%20%5Cfrac%7Bx_1%2Bx_2%7D%7B2%7D%2C%20%5Cfrac%7By_1%2By_2%2C%7D%7B2%7D%20%29)
Plug in the points to get:
![( \frac{ - 3+5}{2}, \frac{ - 2+4}{2} )](https://tex.z-dn.net/?f=%28%20%5Cfrac%7B%20-%203%2B5%7D%7B2%7D%2C%20%5Cfrac%7B%20-%202%2B4%7D%7B2%7D%20%29)
![( \frac{ -2}{2}, \frac{ 2}{2} )](https://tex.z-dn.net/?f=%28%20%5Cfrac%7B%20-2%7D%7B2%7D%2C%20%5Cfrac%7B%202%7D%7B2%7D%20%29)
![( - 1, 1)](https://tex.z-dn.net/?f=%28%20%20-%201%2C%201%29)
We find the radius of the circle using the center (-1,1) and the point (5,-2) on the circle using the distance formula:
![r = \sqrt{ {(x_2-x_1)}^{2} + {(y_2-y_1)}^{2} }](https://tex.z-dn.net/?f=r%20%3D%20%20%5Csqrt%7B%20%7B%28x_2-x_1%29%7D%5E%7B2%7D%20%2B%20%7B%28y_2-y_1%29%7D%5E%7B2%7D%20%7D%20)
![r = \sqrt{ {(5 - - 1)}^{2} + {( - 2- - 1)}^{2} }](https://tex.z-dn.net/?f=r%20%3D%20%20%5Csqrt%7B%20%7B%285%20-%20%20-%201%29%7D%5E%7B2%7D%20%2B%20%7B%28%20-%202-%20-%201%29%7D%5E%7B2%7D%20%7D%20)
![r = \sqrt{ {(6)}^{2} + {( - 1)}^{2} }](https://tex.z-dn.net/?f=r%20%3D%20%20%5Csqrt%7B%20%7B%286%29%7D%5E%7B2%7D%20%2B%20%7B%28%20-%201%29%7D%5E%7B2%7D%20%7D%20)
![r = \sqrt{ 36+ 1 } = \sqrt{37}](https://tex.z-dn.net/?f=r%20%3D%20%20%5Csqrt%7B%2036%2B%201%20%7D%20%20%3D%20%20%5Csqrt%7B37%7D%20)
The equation of the circle is given by:
![(x-h)^2 + (y-k)^2 = {r}^{2}](https://tex.z-dn.net/?f=%28x-h%29%5E2%20%2B%20%28y-k%29%5E2%20%3D%20%20%7Br%7D%5E%7B2%7D%20)
Where (h,k)=(-1,1) and r=√37 is the radius
We plug in the values to get:
![(x- - 1)^2 + (y-1)^2 = {( \sqrt{37}) }^{2}](https://tex.z-dn.net/?f=%28x-%20-%201%29%5E2%20%2B%20%28y-1%29%5E2%20%3D%20%20%7B%28%20%5Csqrt%7B37%7D%29%20%7D%5E%7B2%7D%20)
![(x + 1)^2 + (y - 1)^2 = 37](https://tex.z-dn.net/?f=%28x%20%2B%201%29%5E2%20%2B%20%28y%20-%201%29%5E2%20%3D%2037)
We expand to get:
![{x}^{2} + 2x + 1 + {y}^{2} - 2y + 1 = 37](https://tex.z-dn.net/?f=%20%7Bx%7D%5E%7B2%7D%20%20%2B%202x%20%20%2B%201%20%2B%20%20%7By%7D%5E%7B2%7D%20%20-%202y%20%2B%201%20%3D%2037)
![{x}^{2} + {y}^{2} + 2x - 2y +2 - 37= 0](https://tex.z-dn.net/?f=%7Bx%7D%5E%7B2%7D%20%20%20%2B%20%20%7By%7D%5E%7B2%7D%20%2B%20%202x%20%20-%202y%20%2B2%20-%2037%3D%200)
![{x}^{2} + {y}^{2} + 2x - 2y - 35= 0](https://tex.z-dn.net/?f=%7Bx%7D%5E%7B2%7D%20%20%20%2B%20%20%7By%7D%5E%7B2%7D%20%2B%20%202x%20%20-%202y%20%20%20-%20%2035%3D%200)
We want to find at least four points on this circle.
We can choose any point for x and solve for y or vice-versa
When y=0,
![{x}^{2} + {0}^{2} + 2x - 2(0) - 35= 0](https://tex.z-dn.net/?f=%7Bx%7D%5E%7B2%7D%20%20%20%2B%20%20%7B0%7D%5E%7B2%7D%20%2B%20%202x%20%20-%202%280%29%20%20-%20%20%2035%3D%200)
![{x}^{2} +2x - 35= 0](https://tex.z-dn.net/?f=%7Bx%7D%5E%7B2%7D%20%20%20%2B2x%20%20%20-%20%20%2035%3D%200)
![(x - 5)(x + 7) = 0](https://tex.z-dn.net/?f=%28x%20-%205%29%28x%20%2B%207%29%20%3D%200)
![x = 5 \: or \: x = - 7](https://tex.z-dn.net/?f=x%20%3D%205%20%5C%3A%20or%20%5C%3A%20x%20%3D%20%20-%207)
The point (5,0) and (-7,0) lies on the circle.
When x=0
![{0}^{2} + {y}^{2} + 2(0) - 2y - 35= 0](https://tex.z-dn.net/?f=%7B0%7D%5E%7B2%7D%20%20%20%2B%20%20%7By%7D%5E%7B2%7D%20%2B%20%202%280%29%20%20-%202y%20%20%20-%20%2035%3D%200)
![{y}^{2} - 2y - 35= 0](https://tex.z-dn.net/?f=%20%7By%7D%5E%7B2%7D%20-%202y%20%20%20-%20%2035%3D%200)
![(y - 7)(y + 5) = 0](https://tex.z-dn.net/?f=%28y%20-%207%29%28y%20%2B%205%29%20%3D%200)
![y = 7 \: or \: y = - 5](https://tex.z-dn.net/?f=y%20%3D%207%20%5C%3A%20or%20%5C%3A%20y%20%3D%20%20-%205)
The point (0,-5) and (0,7) lie on this circle.